Monitoring Coastal Erosion in Cyprus: An Analysis Utilizing Sentinel-1 SAR Data - Melillos, George; Kalogirou, Eleftheria; Hadjimitsis, Diofantos G.; Schwarz, Egbert; Wiehle, Stefan (My University, 2023)
The maritime safety and security of coastal regions is a crucial concern impacted by the dynamic growth and erosion processes shaping these areas. Coastal erosion can pose a safety risk to people living or working in these areas and the tourism industry. Furthermore, erosion can include hazards to maritime infrastructure, such as piers, ports, and other facilities, as well as to shipping and navigation in the area. Problems that can be identified from coastal erosion and accretion are changes in water depth, unpredictable currents, displacement of buoys and markers, increased risk of vessel grounding as well as changes in shoreline characteristics that can affect the direction and intensity of wind and waves, making it difficult for ships and boats to navigate safely. This paper uses Sentinel 1 satellite data to monitor Coastal Erosion patterns along the Southeast Cyprus coastlines. The findings of this study could help manage coastal resources and improve maritime safety and security in Cyprus. This study thereby contributes to the broader body of knowledge concerning coastal erosion monitoring using satellite-based remote sensing data, explicitly emphasising the application of Sentinel-1 SAR imagery. The study's methodologies and findings provide valuable insights that can be extended to other similar coastal regions in Cyprus.
Keywords: Coastal erosion; Sentinel 1 SAR; Sentinel Application Platform (SNAP); Southeast Cyprus coastlines